Personality Shadows: Dark Triad Traits and Academic Major Choices Among Greek University -Students - Constantinos M. Kokkinos; Ioanna Voulgaridou; Costas N. Tsouloupas (International Journal of Educational Psychology)
This study examined the link between academic majors and Dark Triad personality traits in 2,387 Greek university students. Utilizing Bifactor Exploratory Structural Equation Modeling, we identified a general dark factor (D-factor) and three specific traits. Latent Profile Analysis revealed four personality clusters: self-centric personalities, ambitious manipulators, tactful manipulators, and omni-dark personalities. Self-centric personalities exhibited low D-factor levels but high narcissism, typically choosing majors like Humanities, Law, and Social Sciences that spotlight personal success. Tactful manipulators, with moderate Machiavellianism and narcissism but low psychopathy, opted for majors in Humanities, Law, Social Sciences, Economics, and Information Sciences, suitable for roles demanding influence and leadership. Ambitious manipulators displayed high Machiavellianism and narcissism with lower psychopathy, favoring competitive fields like Maths, Natural/Technological Sciences, and Health/Life Sciences, which offer opportunities for personal advancement and leadership. Omni-dark personalities scored high across all Dark Triad traits, gravitating towards majors linked with power and competitive hierarchies. The study also found a higher prevalence of omni-dark personalities among males, suggesting potential biological, social, and cultural influences. These insights inform potential interventions to support students in their educational and developmental paths.